Official Legal Translation at the International Criminal Court: Quality Standards and Challenges: الترجمة القانونية الرسمية لدى المحكمة الجنائية الدولية: معايير الجودة والتحديات - Abbaci , Adel (Maalim, 2026)
Official legal translation constitutes a fundamental process at the International Criminal Court (ICC), as it receives attention as part of its keenness to raise the level of visibility of its international judicial activity and its contribution to the protection of human rights. The importance of such translation is further underscored by the way it is organized within the Court itself, as well as by the large volume of official translations it produces, including judgments, decisions, orders and other materials related to the various international crimes brought before it. This article aims to explore the various quality standards of official legal translations at the International Criminal Court, as well as the various challenges they face. In order to achieve the required quality in official translations, the ICC relies on a set of diverse standards that guide the translation process, thereby ensuring the issue of accurate and reliable translations. However, a number of challenges confront the official legal translation at this court, making it a highly complex process that can only be implemented by balancing adherence to these standards with developing procedures to overcome these challenges.